Circular concrete: validating new technologies in the lab and on-site - Bram Dooms; Jeroen Vrijders (Acta Polytechnica CTU Proceedings, 2022)
The growing importance of a circular economy also holds possibilities for concrete. Some of the principles of circularity, like the re-use of "waste" as secondary raw material and the optimisation of the design with regards to lifespan, environmental impact and re-use, can be applied. Several technological innovations in this domain are in an advanced stage of development. However, the transition from research to full commercial applications is held back, mostly due to the absence of documented experience and the lack of a technical framework (prescriptions). In order to accelerate the adoption of new technologies, the Belgian Building Research Institute (BBRI) started the project "Circular.Concrete". In this paper, the results are presented of validation tests regarding 1) smart crushing technology, 2) the carbonation of recycled aggregates, 3) concrete using only recycled aggregates and 4) the use of alternative binders and supplementary cementitious materials.